IMPLIKASI HUKUM PENERAPAN APPRAISAL RIGHTS (HAK MEMINTA SAHAM DIBELI) DALAM MERGER BANK DANAMON DAN BANK NUSANTARA PARAHYANGAN - Cahya Utami Aldana (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2026)
The 2019 merger between Bank Danamon and Bank Nusantara Parahyangan (BNP) raised a fundamental issue regarding the effectiveness of appraisal rights as a legal protection mechanism for minority shareholders. Although these rights are normatively regulated under Article 62 of the Indonesian Company Law (Law No. 40 of 2007) and the Financial Services Authority Regulation (POJK) No. 74/POJK.04/2016, their implementation in practice tends to be formalistic and has not fully ensured substantive justice. This study aims to analyze the application of appraisal rights in the Danamon–BNP merger and its legal implications for the protection of minority shareholders. The research employs a normative juridical method with statutory, conceptual, and comparative approaches. The findings reveal that although the merger procedure formally complies with existing regulations, its implementation does not fully reflect the fairness principle within good corporate governance. Limited transparency in fair value determination and weak supervisory oversight by the Financial Services Authority (OJK) have created potential inequities in protecting minority shareholders’ economic rights. Therefore, regulatory reform is required to enhance valuation transparency and strengthen OJK’s supervisory role, ensuring that appraisal rights function effectively as an instrument of corporate justice within Indonesia’s banking sector.